Who cares for the bereaved? A national survey of family caregivers of people with motor neurone disease. Issue 1 (2nd January 2021) - Aoun, Samar M.; Cafarella, Paul A.; Rumbold, Bruce; Thomas, Geoff; Hogden, Anne; Jiang, Leanne; Gregory, Sonia; Kissane, David W.
Abstract: Background: Although Motor Neurone Disease (MND) caregivers are most challenged physically and psychologically, there is a paucity of population-based research to investigate the impact of bereavement, unmet needs, range of supports, and their helpfulness as perceived by bereaved MND caregivers. Methods : An anonymous national population-based cross-sectional postal and online survey of bereavement experiences of family caregivers who lost a relative/friend to MND in 2016, 2017, and 2018. Recruitment was through all MND Associations in Australia. Results : 393 valid responses were received (31% response rate). Bereaved caregiver deterioration in physical (31%) and mental health (42%) were common. Approximately 40% did not feel their support needs were met. Perceived insufficiency of support was higher for caregivers at high bereavement risk (63%) and was associated with a significant worsening of their mental and physical health. The majority accessed support from family and friends followed by MND Associations, GPs, and funeral providers. Informal supports were reported to be the most helpful. Sources of professional help were the least used and they were perceived to be the least helpful. Conclusions : This study highlights the need for a new and enhanced approach to MND bereavement care involving a caregiver risk and needs assessment as a basis for a tailored "goodness of fit" support plan. This approach requires continuity of care, more resources, formal plans, and enhanced training for professionals, as well as optimizing community capacity. MND Associations are well-positioned to support affected families before and after bereavement but may require additional training and resources to fulfill this role.